Determinants of sustainable integrated cattle-rice farming systems in Indonesia - AFRIZAL MALIK; AGUS SETIADI; JOKO MARIYONO; SUTARYO SUTARYO (Asian Journal of Agriculture, 2026)
Abstract. Malik A, Setiadi A, Mariyono J, Sutaryo S. 2026. Determinants of sustainable integrated cattle-rice farming systems in Indonesia. Asian J Agric 10 (1): g100168. https://doi.org/10.13057/asianjagric/g100168. The Agricultural System Integrated Cattle-Rice Farming (ASICRF) represents a strategic approach to promoting sustainable agricultural development through the optimization of local resource utilization and the improvement of farm performance. This study employs a Structural Equation Modeling-Partial Least Squares (SEM-PLS) approach to examine the determinants of ASICRF sustainability within a performance-mediated framework. Data were collected from 280 farmers practicing ASICRF across four major rice and cattle (Bos indicus) production districts in Central Java Province, Indonesia. In the proposed model, sustainability is specified as the endogenous variable, system performance as the mediating variable, and technical production practices, farm economics, institutional systems, and environmental and resource factors as exogenous variables. The results indicate strong explanatory power, with R2 values of 0.709 for system performance and 0.742 for system sustainability. Technical production practices, institutional systems, and environmental and resource factors significantly and positively affect system performance, with environmental and resource factors exerting the strongest influence. In contrast, farm economics does not significantly affect system performance. System performance is confirmed as a key mediating variable linking upstream determinants to sustainability outcomes. These findings suggest that sustainability in ASICRF is closely associated with improvements in overall system performance rather than relying solely on technical or economic inputs. In the context of ASICRF, sustainability may reflect farmers’ perceived ability to continuously adopt the system, use resources more efficiently, maintain stable productivity, and generate long-term farm income. However, these results should be interpreted with caution because they are based on self-reported perceptual data from ASICRF farmers selected using non-probability sampling methods. Overall, the study provides empirical insight that may inform the design of context-specific policies and development strategies aimed at strengthening the long-term sustainability of integrated farming systems.